2015
DOI: 10.1080/00480169.2014.963830
|View full text |Cite
|
Sign up to set email alerts
|

Development of integrated surveillance systems for the management of tuberculosis in New Zealand wildlife

Abstract: Disease surveillance for the management of bovine tuberculosis (TB) in New Zealand has focussed, to a large extent, on the development of tools specific for monitoring Mycobacterium bovis infection in wildlife. Diagnostic techniques have been modified progressively over 30 years of surveillance of TB in wildlife, from initial characterisation of gross TB lesions in a variety of wildlife, through development of sensitive culture techniques to identify viable mycobacteria, to molecular identification of individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…In cases where eradication of an animal disease has been undertaken, the disease in question has often been characterized by highly visible epidemics in livestock and/or wildlife (James, ; Klepac, Metcalf, McLean, & Hampson, ); by comparison, M. bovis infection in possums is characterized by a form of tuberculosis involving a long disease course and low overall prevalence among infected populations (Nugent, Buddle et al., ), making it difficult and expensive to detect (especially where possum densities have been reduced to low levels by previous population control). The quantitative Proof of Freedom framework (Anderson et al., , ) was developed specifically by our group to determine the likelihood of successful eradication of M. bovis from local possum populations, part of which involves the use of a probabilistic stopping threshold; but until now this has utilized a set stopping threshold without a clear basis for optimization. To extend this, we therefore assumed a variable stopping threshold could be applied, and then provided some insight into factors that should be considered when setting variable stopping thresholds for differing scenarios.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In cases where eradication of an animal disease has been undertaken, the disease in question has often been characterized by highly visible epidemics in livestock and/or wildlife (James, ; Klepac, Metcalf, McLean, & Hampson, ); by comparison, M. bovis infection in possums is characterized by a form of tuberculosis involving a long disease course and low overall prevalence among infected populations (Nugent, Buddle et al., ), making it difficult and expensive to detect (especially where possum densities have been reduced to low levels by previous population control). The quantitative Proof of Freedom framework (Anderson et al., , ) was developed specifically by our group to determine the likelihood of successful eradication of M. bovis from local possum populations, part of which involves the use of a probabilistic stopping threshold; but until now this has utilized a set stopping threshold without a clear basis for optimization. To extend this, we therefore assumed a variable stopping threshold could be applied, and then provided some insight into factors that should be considered when setting variable stopping thresholds for differing scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Our simulations further suggested that where disease surveillance is inexpensive (e.g., because the cost per surveillance unit is low and/or because the surveillance sensitivity per unit is high), then the optimal stopping threshold will be higher rather than lower—in other words—it would be cheaper, on average, to minimize the risk of failure (i.e., making a false declaration of freedom from M. bovis infection) than it would be to remedy any such failure. Although we compared only two alternative surveillance tools here (leg‐hold traps alone, or DDs (chew‐cards) with follow‐up trapping), there are other options for surveillance of residual M. bovis infection in possums in New Zealand—most notably—the use of wildlife spillover hosts as sentinels for persistent infection (e.g., feral pigs and ferrets and wild deer; Nugent, ; Anderson et al., ). In particular, feral pigs are especially sensitive detectors of persistent M. bovis infection in possums (Nugent, Gortazar, & Knowles, ; Nugent, Whitford, & Young, ; Nugent, Yockney, Whitford, & Cross, ), so where they are abundant and inexpensive to procure—a high stopping threshold would be optimal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are some published examples in which imperfect‐detection modeling has been used to underpin the management of a cryptic wildlife disease (Anderson et al. , ).…”
Section: Introductionmentioning
confidence: 99%